A practical solution to cable bolting problems at the Tsumeb Mine - W. H. Stheeman (Canadian Institute of Mining, Metallurgy and Petroleum, 1982)
"The high rock pressures at the deeper levels of the Tsumeb Mine have necessitated the changing of the mining methods and the introduction of cable bolts. After two rockfalls in the cable-bolted stopes, the mechanics of cable bolting were investigated. Practical methods were developed to find the best grout mixtures, the bond stresses between cables and cement, the bond stresses between rock and cement and the load on the cable bolts, which was mathematically calculated from data observed underground. The design of the cable bolt support system as used at the Tsumeb Mine is explained. GeneralThe Tsumeb Mine is in northern South West Africa/Namibia, approximately 400 km by road from the capital city, Windhoek, at an elevation of 1300 m above sea level. Mining operations in Tsumeb were started in 1905 by the Otavi Minen und Eisenbahn Gesellschaft and continued, with an interruption during the Depre ssion, until 1940, when the mine was closed and taken over by the Custodian of Enemy Property. The present owner, Tsumeb Corporation Limited, obtained the mine in 1947 and restarted the underground mining operations in 1949 after the mine was dewatered. Currently, the stoping operations are between 26 Level (840 m below surface) and 38 Level (1260 m below surface). In addition, the mine is an important silver producer and has produced 670,100 kg of silver since 1947."